Exploring the self-preparedness of frontline healthcare workers in a low- and middle-income country from a humanitarian context during the COVID-19 pandemic: A constructivist grounded theory study - Khan, Farzana; Azad, Tasnim B.; Bhuyian, Saiduzzaman; Karim, Hasina; Grant, Liz (Frontiers in Public Health, 2023)
Background: While much has been written and researched on the availability, accessibility and affordability of personal protective equipment for health workers during the COVID-19 pandemic, there is very little evidence on the ways in which humanitarian health workers see themselves, and engage in self-preparedness for social, physical, mental health and practical care. We sought to address this gap. Methods: We followed a constructivist grounded theory approach to guide in-depth interviews with thirty frontline doctors, nurses and community health workers recruited from the Rohingya refugee camps, Bangladesh, using purposive and snowball sampling. Analysis was carried out through the identification of codes in three phases: an initial line-by-line open coding, next focused axial coding, and finally selective coding. Findings: An emergent-grounded theory of ‘Navigating Self-Preparedness through Pandemics’ was developed as we built a five-phased theoretical framework with the following pillars: (a) Pandemic Shock; (b) Pandemic Awareness; (c) Pandemic Learning; (d) Pandemic Resilience and (e) Pandemic Resurgence. Interpretation: The theory emerged as a realistic, socially, and culturally sensitive COVID-19 strategy to support health workers. Self-preparedness was characterized by two interwoven processes: 1) the experiences of the daily life span of health workers trying to improve their own protection using all their potential while providing care for patients in a vulnerable setting and time, and 2) the inseparable nature of physical, psychological, social and spiritual factors for each stage of learning during pandemic to achieve better outcomes. Funding: NIHR Global Health Research Unit on Respiratory Health (RESPIRE), Usher Institute, University of Edinburgh, UK.